Dissolved major element concentration data of the Equatorial Pacific Ocean transect during RV SONNE cruise SO298 - Edel Mary O extquotesingleSullivan; Zvi Steiner (PANGAEA, 2025)
This dataset presents absolute salinity-normalized dissolved major element (Ca, Mg, K, Sr, Li) concentrations along RV SONNE cruise track SO298 along the Equatorial Pacific Ocean collected during GEOTRACES GP11 expedition (Guayaquil, Ecuador - Townsville, Australia) from April 14th to June 2nd, 2023. Samples were collected from the trace-metal clean Ti-frame rosette equipped with a Kevlar-coated winch. Samples were filtered through 0.2 μm AcroPak™ 500 filter capsules, collected in acid-cleaned 4 mL PP tubes, and acidified to pH ~2 with trace metal-grade HCl. Samples were analysed for Na, Ca, Mg, K, Li and Sr using a Varian-720 ES ICP-OES. Samples were diluted by a factor of 78-82 in 0.12 M HCl to the same final salinity. Multiple spectral lines were selected for each element, and samples were corrected for instrumental drift by sample-standard bracketing with IAPSO P166 diluted to the same final salinity. Calibration was performed on 7 dilutions of IAPSO P166. Element-to-sodium ratios were calculated for all combinations of spectral lines. Assuming a constant Na-to-salinity (PSU)=35 ratio, the element/Na ratios were multiplied by 0.46847 μmol kg-1 to obtain the salinity (PSU)-normalized element concentration, and by the ratio of practical to absolute salinity (TEOS-10). The TEOS-10 absolute salinities were calculated from EOS-80 values using the Gibb extquotesingles Oceanographic Toolbox using the R package extquotesinglegsw extquotesingle (v 1.1-1).